Enzyme Induction - Parke, Dennis (Basic Life Sciences, 1975)
The book is the outgrowth of a worsshop conference on Molecular Mechanisms for repair of DNA. That a book on DNA repair to document that discussion would be useful to researcher in this field and in related fieldss. El texto trata específicamente de l colesterol y sus efectos en la sangre, es extremadamente importante y vale la pena examinar el texto para determinar las acciones reguladoras .